Pengaruh Struktur Organisasi Terhadap Kualitas Sistem Informasi Akuntansi Pada Pt. Kunci Inti Transindo Jakarta - Rosmiati, Imas; Kuraesin, Arlis Dewi (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
Changes in an accounting information system always depend on an organizational structure, and the quality of the accounting information system will affect the success of the organizational structure. The purpose of conducting this research is to determine the extent of the influence of the Organizational Structure on the Quality of the Accounting Information System at PT. Kunci Inti Transindo Jakarta. The research results are expected to prove that the given model can be used as a solution to the quality problems of the accounting information system. In this study the population is PT.Kunci Inti Transindo located in North Jakarta with 89 employees. The sample obtained is by using a data collection technique by giving a questionnaire to the employees of PT. Kunci Inti Transindo Jakarta's core. The method used in analyzing the data is a simple linear regression analysis method and through a quantitative approach. The results prove that the Organizational Structure has a positive effect on the Quality of the Accounting Information System by 81.4%. and the remaining 18.6% is influenced by factors other than this study. This means that a quality organizational structure will result in a maximally integrated information system.. Key words: Structure, organization, and quality, information system, accounting